2015
DOI: 10.1016/j.fm.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analysis of Oenococcus oeni PSU-1 response to ethanol shock

Abstract: The correct development of malolactic fermentation depends on the capacity of Oenococcus oeni to survive under harsh wine conditions. The presence of ethanol is one of the most stressful factors affecting O. oeni performance. In this study, the effect of ethanol addition (12% vol/vol) on O. oeni PSU-1 has been evaluated using a transcriptomic and proteomic approach. Transcriptomic analysis revealed that the main functional categories of the genes affected by ethanol were metabolite transport and cell wall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…About 14% of the proteins observed by Olguín et al . (), that decrease in concentration, are related to cell envelope biogenesis; one of them, dTDPD‐ glucose 4,6‐dehydratase (RmlB), is involved in cell wall lipopolysaccharide biosynthesis and was detected previously by Silveira et al . () in the membrane‐associated protein extract of cells pre‐adapted in 8% ethanol but not in the control condition or after 1 h of 12% ethanol stress.…”
Section: Ethanol Stress Response In Oenococcus Oenimentioning
confidence: 95%
See 2 more Smart Citations
“…About 14% of the proteins observed by Olguín et al . (), that decrease in concentration, are related to cell envelope biogenesis; one of them, dTDPD‐ glucose 4,6‐dehydratase (RmlB), is involved in cell wall lipopolysaccharide biosynthesis and was detected previously by Silveira et al . () in the membrane‐associated protein extract of cells pre‐adapted in 8% ethanol but not in the control condition or after 1 h of 12% ethanol stress.…”
Section: Ethanol Stress Response In Oenococcus Oenimentioning
confidence: 95%
“…Olguín et al . () used a microarray‐based transcriptomic approach to evaluate cell response to ethanol. Their results revealed that transport systems, such as carbohydrates, inorganic ions and amino acid (especially those for glutamate and/or aminobutyrate) transporters, genes related to cell wall and membrane component biosynthesis, such as mreB (coding an essential protein for cell morphogenesis) and acetylmuramidase genes were widely and negatively affected by ethanol stress.…”
Section: Ethanol Stress Response In Oenococcus Oenimentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Campbell-Sills et al (2015) reviewed the population structure of many O. oeni strains using comparative genomics, and confirmed that the distribution of 50 strains can be divided into two major groups, according to their ecological niche: wine or cider. Transcriptomic and proteomic analyses of O. oeni strains cultivated under wine-simulated conditions showed that the environment strongly affects O. oeni stress-responses at both levels (Costantini et al, 2015; Olguín et al, 2015). Despite the bioinformatic tools employed for these studies, a full systemic understanding of the metabolic capabilities and behavior of this malolactic bacterium under extreme environments would strongly benefit from the reconstruction of a genome–scale metabolic model able to integrate the current knowledge of this LAB.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, genotypic characterization of different strains of O. oeni, isolated from diverse geographic regions during the process of malolactic fermentation, revealed a highly diverse genetic background among the strains derived from different locations, but also strains categorized in the same phylogenetic group were detected in diverse regions, adapted in the same type of wine [105]. Noteworthy, the genomic, transcriptomic, and proteomic profile of various O. oeni strains was found to be strongly influenced by microenvironmental conditions during winemaking [106][107][108].…”
Section: Combination Of Microbial Evolution Studies With Metabolism Amentioning
confidence: 99%